Affine matching of two sets of points in arbitrary dimensions - Tanács, Attila; Czédli, Gábor; Palágyi, Kálmán; Kuba, Attila (Acta Cybernetica, 2001)
In many applications of computer vision, image processing, and remotely sensed data processing, an appropriate matching of two sets of points is required. Our approach assumes one-to-one correspondence between these sets and finds the optimal global affine transformation that matches them. The suggested method can be used in arbitrary dimensions. A sufficient existence condition for a unique transformation is given and proven.